Sprint development practices in elite football code athletes. Issue 1 (February 2022) - Nicholson, Ben; Dinsdale, Alex; Jones, Ben; Heyward, Omar; Till, Kevin
Despite the importance and complexity of developing sprint performance in football code athletes, there are limited studies exploring practitioners' practices to improves Sprinting. Therefore, this study aimed to describe and evaluate the practices used with elite football code athletes to develop sprint performance. Ninety subjects completed a survey comprised of four sections (coaching demographic, evaluation of training, organisation of training, and training protocols). Survey responses showed that 98% of practitioners monitor sprint performance, and 92% integrated monitoring strategies into sprint development programmes to inform training. All practitioners used combined training methods including specific (e.g., sprints with or without overload) and non-specific (e.g., strength training or plyometrics) methods targeting the underpinning determinants of sprint performance. Most practitioners reported prescribing 1–3 or 2–4 days · wk −1 for sprint development, both in-season and pre-season. Sprint development programmes were uncommon in the off-season. Most specific sprint training sessions were reportedly shorter in duration (5–15 and 15–30min) than non-specific sprint training methods (30–45 and >45min) irrespective of the season phases. Sprint development was integrated before and after sport-specific training, regularly using warm-ups and gym sessions. Specific training methods were also implemented in separate sessions. The specific content (e.g., exercise selection, training load prescription) was highly variable between practitioners. This study represents the first detailed survey (practices and justification) of sprint development practices (evaluation and organisation of training protocols) in football code cohorts. These findings present multiple methods of structuring, integrating and manipulating sprint training based on the training aims and the individual context.